PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PEMENUHAN KEBUTUHAN INFORMASI (Survei Terhadap Akun Twitter @HabisNontonFilm) - Mohammad Fachrul Rozy, (2024)
In an increasingly advanced era, information can be accessed more easily. One of the information source is the media social Twitter. Through Twitter, there is a lot of information that can be obtained and one of them is information about films. One of the account who provides information about films is @HabisNontonFilm. This research aims to find out how much influence the use of Twitter social media has on fulfilling the information needs of followers of the @HabisNontonFilm account. The theory used in this research is the Information Seeking Theory proposed by Wilson regarding information seeking. This research uses an explanatory quantitative method using a survey method via Google Form. The statements in the survey were first tested for validity and reliability and then distributed to 100 respondents who met the specified criteria. Based on the analysis test, the coefficient of determination test results were found to be 40.3%, which means that the influence of the use of social media Twitter @HabisNontonFilm on fulfilling the information needs of their followers is 40.3% and the remaining is 59. 7% is influenced by other variables that are not in the research. The results of the hypothesis test show T count 8.140 > t table 1.960, which means the hypothesis is accepted and there is a significant influence from the use of social media Twitter @HabisNontonFilm on fulfilling the information needs of their followers.